Interconnected Tolerancing Activities and the Role of Key Characteristics - Horber, Dennis; Götz, Stefan; Wartzack, Sandro (Research in Tolerancing, 2024)
Products are nowadays characterized by rising complexity, so that companies need to adapt their development processes to resulting challenges. Transferring this need for adaption to the tolerancing domain, new approaches are expected to enable companies to tackle increasing quality demands and costs pressures. Resulting from that, a variety of tolerancing activities exist, which are closely interconnected with the product development process. Their application leads to several artifacts, which can be gathered in a digital thread weaving through the processes. As most of these approaches are document-centered, new progresses in model-based systems engineering offer unused potential to ensure traceable processes. This chapter therefore presents an approach for the model-based formalization of tolerancing activities to contribute to this digital thread. Furthermore, a holistic approach for a common key characteristic model is described, which is used along with the formalized activities. Due to their importance for tolerancing, key characteristics are a profound basis for enabling traceability and the approach ensures a thorough link. It includes the systematic and automated derivation of key characteristics from requirements using natural language processing, their further extension and prioritization.<br